Legal Certainty on the Dissemination of Defamatory Content on Social Media: A Case Analysis of a Flogging Procession Recording in Aceh - Siregar, Friska Anggi; Yulis, Sari; Masyitah, Masyitah (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2025)
The public implementation of flogging in Aceh is a manifestation of Islamic law that has been practiced since the time of Prophet Muhammad SAW, where the process aimed to deter society at large. However, in the digital era, the dissemination of recordings of such punishments through social media has sparked legal controversy concerning privacy violations and defamation, with broad impacts on the convicted individuals. This study aims to analyze the legal certainty regarding the distribution of flogging punishment content in digital spaces and to examine the intersection between Islamic law and Indonesia’s national law. This article is a qualitative library research, using a normative legal study methodology with a descriptive-analytical approach. The results show that the dissemination of flogging punishment recordings in Aceh via social media creates complex legal issues because, although public flogging is legally justified under Islamic law and the Qanun Jinayat, its digital distribution has the potential to violate privacy and defame individuals according to the provisions of the Electronic Information and Transactions Law (ITE Law) and the Indonesian Criminal Code (KUHP). Therefore, specific regulations are urgently needed to integrate Islamic law principles with national law to ensure the protection of human rights and to prevent the misuse of content in the global and permanent nature of digital public spaces.